Disentangling food transformation narratives: a Q-method analysis on pathways to sustainable food systems and their implications - Mull, Meredith L.; Torralba, Mario (Frontiers in Nutrition, 2025)
IntroductionWhile the urgency to transform global food systems is widely recognized in scientific and policy circles, differing interpretations of what constitutes a sustainable food system continue to challenge coordinated action. Understanding these diverse perspectives is essential for designing inclusive and effective transformation pathways.MethodsThis exploratory study used Q-methodology to investigate how university students enrolled in sustainability-related programs conceptualize sustainable food systems. Participants sorted and ranked statements reflecting various food system priorities, enabling the identification of shared and divergent viewpoints.ResultsAnalysis revealed five distinct narratives: (1) securing food sovereignty, (2) contributing to climate justice, (3) doing no harm, (4) empowering consumers, and (5) connecting people to their food. Despite these differences, consensus emerged around the importance of food security and transparent, democratic governance. In contrast, elements such as urban agriculture, GMOs, and the preservation of food traditions were consistently deprioritized.DiscussionThe findings highlight the value of incorporating plural perspectives into food system research and policy. Consensus elements may serve as bridging concepts to foster dialogue and collaboration across diverse stakeholder groups. The deprioritization of certain themes underscores the need for context-sensitive approaches that reflect the lived experiences and priorities of specific populations.